Feminism and Gestational Surrogacy. Theoretical Reconsiderations in the Name of the Child and the Woman - Bandelli, Daniela (Italian Sociological Review, 2019)
This article discusses the limits of the feminist theory of commodification of women’s body in contrasting the diffusion of gestational surrogacy as a new reproductive practice and women’s labour. Feminist scholars and activists argue that surrogacy needs to be banned to protect the unitarity of motherhood and the dignity of women. In assuming that surrogates are victims of unbalanced power relations this theoretical perspective obscures women’s decision-making process to engage in free actions, which can be nevertheless detrimental to the female subject’s and other people’s wellbeing. In fact, full autonomy of women in deciding how to use their bodies and reproductive capacity is the theoretical underpinning of so-called liberal feminists who are in favour of legalization and regulation of the practice. In this article I suggest acknowledging surrogates’ agency, posit them as subjects of social actions, and reclaim the need to protect the child as the only subject with ‘no choice’.